2010
DOI: 10.1249/mss.0b013e3181d9eea0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Chondral Defects in Athletes' Knees

Abstract: Full-thickness focal chondral defects in the knee are more common in athletes than among the general population. More than one-half of asymptomatic athletes have a full-thickness defect. Further study is needed to define more precisely the prevalence of these lesions in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
281
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 401 publications
(292 citation statements)
references
References 48 publications
5
281
0
6
Order By: Relevance
“…A recent systematic review demonstrated an average prevalence of fullthickness focal chondral defects in 36% of athletes. 49 Defects were located predominantly in the patellofemoral compartment (37%) and femoral condyles (35%), and less frequently on the tibial plateau (25%). Magnetic resonance imaging (MRI) evaluation of asymptomatic professional basketball players revealed articular cartilage abnormalities in the knee of up to 89% of the players, 181 and cartilage injury has been reported to exist in 20% of professional American football players.…”
mentioning
confidence: 99%
“…A recent systematic review demonstrated an average prevalence of fullthickness focal chondral defects in 36% of athletes. 49 Defects were located predominantly in the patellofemoral compartment (37%) and femoral condyles (35%), and less frequently on the tibial plateau (25%). Magnetic resonance imaging (MRI) evaluation of asymptomatic professional basketball players revealed articular cartilage abnormalities in the knee of up to 89% of the players, 181 and cartilage injury has been reported to exist in 20% of professional American football players.…”
mentioning
confidence: 99%
“…Given the prevalence of articular cartilage lesion deficits in the more active population, 22 addressing both functional capacity related to activities of daily living, as well as performance during higher-level activities, may provide new insights for the guidelines for return to sport and other demanding activities, as well as improve long-term outcomes.…”
Section: Implications For Rehabilitation: Functionmentioning
confidence: 99%
“…11,74 Approximately 5% to 27% of patients younger than 45 years of age have articular cartilage lesions identified at arthroscopy, 3,11,31,74 and active individuals may be at even higher risk for articular cartilage injury than the general population. 22 In the short term, these lesions may lead to a loss of function and a significant decline in activity participation. 22,25 Although the T T STUDY DESIGN: Systematic literature review.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a 5-10% incidence of full thickness chondral lesions following acute hemarthrosis (Noyes et al, 1980). In athletes, there is approximately a 36% prevalence of full thickness focal chondral defects, with 14% being asymptomatic (Flanigan et al, 2010). Patients who have symptomatic chondral lesions typically present with pain localized to the compartment of injury, increased with weight-bearing of that compartment.…”
Section: Cartilage Injurymentioning
confidence: 99%